Specific considerations in the treatment of pediatric inflammatory bowel disease. (February 2008) - Grossman, Andrew B; Baldassano, Robert N
Inflammatory bowel disease is one of the most prevalent chronic inflammatory disorders and commonly presents during childhood or adolescence. Occurring during a critical period of growth and development, pediatric Crohn's disease and ulcerative colitis require special consideration. Children often experience growth failure, malnutrition, pubertal delay and bone demineralization. Medical treatment must be optimized to promote clinical improvement and reverse growth failure with minimal toxicity. In addition to pharmacologic and surgical interventions, nutritional therapies play a vital role in the management of pediatric inflammatory bowel disease. This review will outline the epidemiology and clinical complications that are unique to pediatric inflammatory bowel disease, current trends, and recent advances in nutritional and pharmacologic treatment, and projected future therapeutic direction.